Membrane electrode assembly for fuel cell containing plate-shaped porous silica and fuel cell containing same
Incorporating plate-shaped porous silica into the catalyst layer addresses the issue of reduced performance and durability in low humid environments by enhancing moisture retention and ionic conductivity in fuel cells.
Patent Information
- Application Number
- JP2024527270
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-11-26
- Filing Date
- 2022-11-11
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-11-11
AI Technical Summary
Fuel cells face challenges in maintaining performance and durability in low humid environments due to reduced ionic conductivity and moisture loss from the polymer electrolyte membrane.
Incorporation of plate-shaped porous silica into the catalyst layer of the membrane electrode assembly to enhance moisture retention and facilitate mass transfer, with specific dimensions and proportions to optimize performance.
The plate-shaped porous silica effectively retains moisture, maintaining ionic conductivity and improving the durability and performance of the fuel cell in low humidity conditions.
Smart Images

Figure 2024546418000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a membrane electrode assembly for a fuel cell with improved performance in low humidification environments. [Background technology]
[0002] Fuel cells are batteries equipped with a power generation system that directly converts chemical reaction energy, such as the oxidation / reduction reaction of hydrogen and oxygen contained in hydrocarbon fuel substances such as methanol, ethanol, and natural gas, into electrical energy. Due to their high energy efficiency and environmentally friendly characteristics with low pollutant emissions, fuel cells are attracting attention as a next-generation clean energy source to replace fossil energy.
[0003] Fuel cells have the advantage of being able to produce a wide range of output power due to their stack configuration made up of stacked unit cells, and they are attracting attention as a small and portable power source for mobile use because they have an energy density four to ten times that of small lithium batteries.
[0004] The stack that actually generates electricity from the fuel cell has a structure in which several to several tens of unit cells, each consisting of a membrane electrode assembly (MEA) and a separator (also called a bipolar plate), are stacked together. The membrane electrode assembly generally has a structure in which an electrolyte membrane is sandwiched between an oxidizing electrode (anode or fuel electrode) and a reducing electrode (cathode or air electrode) on either side of the membrane.
[0005] Fuel cells can be classified into alkaline electrolyte fuel cells, polymer electrolyte membrane fuel cells (PEMFC), etc. depending on the state and type of electrolyte. Among them, polymer electrolyte fuel cells are attracting attention as portable, vehicle and home power sources due to their advantages such as low operating temperature of less than 100℃, fast start-up and response characteristics and excellent durability.
[0006] Representative examples of polymer electrolyte fuel cells include the Proton Exchange Membrane Fuel Cell (PEMFC), which uses hydrogen gas as fuel, and the Direct Methanol Fuel Cell (DMFC), which uses liquid methanol as fuel.
[0007] To summarize the reactions that occur in a polymer electrolyte fuel cell, first, when fuel such as hydrogen gas is supplied to the oxidizing electrode, hydrogen ions (H+) and electrons (e-) are generated by the oxidation reaction of hydrogen at the oxidizing electrode. The generated hydrogen ions are transferred to the reducing electrode through the polymer electrolyte membrane, and the generated electrons are transferred to the reducing electrode through an external circuit. Oxygen is supplied to the reducing electrode, and the oxygen combines with the hydrogen ions and electrons to generate water through the reduction reaction of oxygen.
[0008] Meanwhile, in order to apply fuel cells to FCVs (Fuel Cell Vehicles), it is essential to miniaturize the fuel cell system, which requires the development of a membrane electrode assembly (MEA) that can provide excellent power density per unit area. In particular, the durability of the MEA catalyst layer needs to be improved for practical operation of FCVs. Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a membrane electrode assembly with improved mass transfer efficiency, and performance and durability in low humidification environments by introducing nanostructured porous silica into a portion of the electrode layer.
[0010] Another object of the present invention is to provide a fuel cell to which said membrane electrode assembly structure is applied, which has improved performance and durability in a low humidification environment. [Means for solving the problem]
[0011] To achieve the above object, a membrane electrode assembly for a fuel cell according to one embodiment of the present invention includes a first catalyst layer including a plate-shaped porous silica and a polymer electrolyte membrane.
[0012] The plate-like porous silica may include mesopores having a morphology perpendicular to the plate-like morphology.
[0013] The plate-like porous silica may have pores with a diameter of 2 to 40 nm.
[0014] The plate-like porous silica may have a size of 50 to 2000 nm and a thickness of 30 to 300 nm.
[0015] In the first catalytic layer, the plate-shaped porous silica may be included in an amount of 1 to 20 wt % based on the total weight of the first catalytic layer.
[0016] The ionomer content of the first catalyst layer may be 34 to 40 wt % based on the total weight of the first catalyst layer.
[0017] The first catalyst layer may have a thickness of 0.2 to 5 μm.
[0018] The first catalyst layer may be located between a second catalyst layer that does not contain or contains a smaller amount of plate-shaped porous silica and the polymer electrolyte membrane.
[0019] The first catalyst layer may have an ionomer content greater than the ionomer content of the second catalyst layer.
[0020] A fuel cell according to another embodiment of the present invention includes the above-described fuel cell membrane electrode assembly. Effect of the Invention
[0021] The membrane electrode assembly of the present invention can effectively contain moisture discharged from the electrolyte membrane through the pores of the plate-shaped porous silica in the catalyst layer, thereby solving the problem of reduced ion conductivity that occurs when the electrolyte membrane dries out in a low-humidity environment. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a diagram showing one shape of plate-like porous silica.
[0023] [Diagram 2] FIG. 2 is a schematic diagram showing a structure in which plate-shaped porous silica is contained in a first catalyst layer.
[0024] [Diagram 3] FIG. 2 is a schematic diagram showing the overall configuration of the fuel cell.
[0025] [Figure 4] 1 is a transmission electron microscope (TEM) photograph of plate-shaped porous silica used in one embodiment of the present invention.
[0026] [Diagram 5] 4 is an optical microscope photograph of the surfaces of a first electrode layer and a second electrode layer manufactured according to an embodiment of the present invention.
[0027] [Figure 6] 1 shows the results of evaluating low humidification performance of membrane electrode assemblies (MEAs) manufactured according to examples and comparative examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;
[0029] According to one aspect of the present invention, there is provided a fuel cell membrane electrode assembly including a catalyst layer comprising plate-shaped porous silica. The catalyst layer may be formed on only one side of a polymer electrolyte membrane, or may be formed on both sides of the polymer electrolyte membrane.
[0030] Fig. 1 is a diagram showing one shape of plate-shaped porous silica. Referring to Fig. 1, the catalyst layer including the plate-shaped porous silica is located in contact with the electrolyte membrane and can effectively contain moisture through the pores of the silica, thereby suppressing water evaporation from the polymer electrolyte membrane, and the polymer electrolyte membrane and the catalyst layer can maintain appropriate humidity in a low humidity environment, which helps to maintain excellent ion conductivity.
[0031] The mesopores of the plate-shaped porous silica may have a shape perpendicular to the plate shape (same direction as the thickness direction). When the pore shape is perpendicular to the plate shape, the pores are arranged perpendicular to the electrolyte membrane, facilitating mass transfer and further improving performance. When the pore shape is horizontal to the plate shape, the pores are arranged parallel to the electrolyte membrane when the electrode is formed in the same shape as existing mesoporous silica, hindering mass transfer and reducing performance.
[0032] The plate-shaped porous silica may be mesoporous silica, specifically, plate-shaped porous silica having pores with a diameter of 2 to 40 nm, 4 to 30 nm, or 6 to 20 nm. If the pore diameter of silica is smaller than 2 nm, the excessively small pores may make it difficult for moisture to penetrate, limiting ion transmission through the pores, and the moisture-containing properties of the porous silica may be reduced, whereas if the pore diameter of silica is larger than 40 nm, moisture that penetrates into the pores does not remain in the pores for a long time and is easily evaporated, so that the performance improvement of the porous silica in a low humidity environment may be negligible.
[0033] The size of the plate-like porous silica may be preferably 50 to 2000 nm, 100 to 1500 nm, 150 to 1000 nm, or 200 to 800 nm. Here, the size of the porous silica means the maximum length of the width of the plate. If the size of the porous silica is larger than the above range, the catalyst and ionomer of the catalyst layer are not evenly distributed and arranged due to the silica that does not participate in the chemical reaction in the catalyst layer, and the content is reduced, resulting in a problem of reduced chemical reaction efficiency of the catalyst layer. In addition, if the size of the porous silica is smaller than the above range, the pores are not easily arranged in a direction perpendicular to the electrolyte membrane, resulting in a problem of impeded mass transfer.
[0034] The thickness of the plate-like porous silica may be preferably 30 to 300 nm, 40 to 250 nm, or 50 to 200 nm. If the thickness of the plate-like porous silica is thinner than the above range, the porous silica structure is easily damaged even by a weak physical external impact, and thus it may be damaged during dispersion and may be no different from the case of adding amorphous silica. If the thickness of the plate-like porous silica is thicker than the above range, the pores may be unnecessarily deep compared to the depth at which moisture can penetrate into the pores, and the porous silica may occupy an unnecessarily large volume in the catalyst layer, which may only reduce the efficiency of the catalyst layer.
[0035] Plate-shaped porous silica can be prepared by a conventional method for preparing porous silica by hydrolysis and condensation reactions and calcination. However, a template for forming a plate-shaped shape, for example, a block copolymer consisting of an aqueous block and a hydrophilic block, can be used, and the template can be hydrolyzed together with a silica precursor and an acid catalyst. Examples of the block copolymer include Pluronic P123 and Pluronic F127. Examples of the silica precursor include, but are not limited to, tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, or a mixture thereof. Examples of the acid catalyst include HCl, acetic acid, nitric acid, and sulfuric acid. The hydrolysis, condensation, and calcination conditions can be appropriately selected from conventional conditions by a person skilled in the art in consideration of reaction conditions and conditions.
[0036] Fig. 2 is a simplified diagram showing the structure of one embodiment of a fuel cell membrane electrode assembly 100 of the present invention. Referring to Fig. 2, the pores of the plate-like porous silica 1 are preferably formed in a direction perpendicular to the plane of the electrolyte membrane 20 in the first catalyst layer 11 containing the silica 1, and when the plate-like porous silica 1 is arranged so that the pores of the plate-like porous silica 1 are perpendicular to the plane of the electrolyte membrane 20, the pores effectively contain the moisture discharged from the electrolyte membrane 20, facilitating material transfer, and thus the wet environment of the electrolyte membrane 20 can be more effectively maintained.
[0037] Although the plate-shaped porous silica helps maintain a moist environment in the membrane electrode assembly in a low humidity environment, it is important that it is included in the catalyst layer at an appropriate ratio since it is not directly involved in the oxidation-reduction reaction of the catalyst layer or in the hydrogen ion conduction. Specifically, the plate-shaped porous silica is preferably included in the first catalyst layer at 1 to 20 wt % based on the total weight of the first catalyst layer. If the plate-shaped porous silica is included in the first catalyst layer at less than 1 wt %, the effect of maintaining a moist environment by the plate-shaped porous silica may be insignificant, and if the plate-shaped porous silica is included in the first catalyst layer at more than 20 wt %, the oxidation-reduction reaction by the catalyst of the catalyst layer may not occur sufficiently, which may reduce the efficiency of the fuel cell.
[0038] The first catalytic layer containing plate-shaped porous silica contains an ionomer, and it is preferable that the ionomer content is greater than that of a typical catalytic layer not containing porous silica for smooth conduction of hydrogen ions. Specifically, the ionomer content of the first catalytic layer is preferably 34 to 40 wt% based on the total weight of the first catalytic layer. If the ionomer content in the first catalytic layer is higher than the above range, it may hinder the supply of fuel to the platinum catalytic active sites, and if the ionomer content in the first catalytic layer is too low, it may hinder the ion transport ability of the catalytic layer.
[0039] The ionomer may include one or more ionomers selected from the group consisting of fluorine-based ionomers and hydrocarbon-based ionomers. The hydrocarbon-based ionomer may be any known hydrocarbon-based polymer, for example, sulfonated derivatives of poly(arylene ether)s (SPAEs), poly(arylene sulfide)s (SPASs), polyimides (SPIs), polybenzimidazoles (PBIs), polyphenylenes (PPs), polyether ether ketone (PEEK). The fluorine-based polymer may be any known fluorine-based polymer, for example, perfluorinated sulfonic acid, polyvinylidene fluoride, hexafluoropropylene, trifluoroethylene, polytetrafluoroethylene, or one of their copolymers.
[0040] However, the ionomer contained in the catalyst layer together with the plate-shaped porous silica preferably has an equivalent weight (EW) of 600 to 1200 for effective ion conductivity of the catalyst layer.
[0041] The thickness of the first catalytic layer containing the plate-shaped porous silica is preferably 0.2 to 5 μm. If the thickness of the first catalytic layer is less than 0.2 μm, the catalytic layer may be so thin that the plate-shaped porous silica is not sufficiently contained therein, and even if the plate-shaped porous silica is contained therein, the chemical reaction of the catalytic layer may not occur sufficiently. On the other hand, if the thickness of the first catalytic layer is more than 5 μm, there may be a problem that the efficiency of the fuel cell is improved by creating a moist environment due to the inclusion of the plate-shaped porous silica, but the efficiency is further reduced due to the lack of catalytic chemical reaction due to the volume occupied by the porous silica.
[0042] Therefore, in order to further improve the efficiency of the catalyst layer, the first catalyst layer containing plate-shaped porous silica is formed only in the portion in contact with the polymer electrolyte membrane, and a structure in which a catalyst layer containing no or a smaller amount of porous silica is additionally laminated can be applied.
[0043] The first catalyst layer may be located between the second catalyst layer and the polymer electrolyte membrane. Here, the second catalyst layer does not contain or contains a smaller amount of plate-shaped porous silica, and it is more preferable in terms of cell performance that the second catalyst layer does not contain or contains almost no plate-shaped porous silica. If the second catalyst layer contains plate-shaped porous silica, the content of the second catalyst layer should be less than that of the first catalyst layer, and may be less than that of the first catalyst layer by 1% by weight or more, for example, 1 to 20% by weight, specifically 5% by weight or more, more specifically 10% by weight or more. FIG. 2 is a simplified diagram showing a membrane electrode assembly 100 according to an embodiment of the present invention, in which a first catalyst layer 11 is formed on one side of a polymer electrolyte membrane 20, and a second catalyst layer 12 containing no or a smaller amount of plate-shaped porous silica is laminated on the first catalyst layer 11 to form a multi-layered catalyst layer 10. FIG. 2 shows only one surface on which the catalyst layer 10 including the first catalyst layer 11 is formed, but multiple catalyst layers may be formed on both surfaces of the polymer electrolyte membrane, and the catalyst layer 10 including the first catalyst layer 11 may be a cathode electrode or an anode electrode, and is not particularly limited.
[0044] The plate-like porous silica further lengthens the hydrogen ion conduction path in the catalyst layer, and when the ionomer penetrates the silica pores due to the porous structure of the silica, hydrogen ion conduction can be further facilitated. Therefore, in order to increase the bonding strength between the catalyst layer and the electrolyte membrane and to facilitate the positioning of the ionomer in the silica pores, it is preferable that the ionomer content of the first catalyst layer 11 in the catalyst layer 10 is greater than that of the second catalyst layer 12, but the present invention is not limited thereto.
[0045] The catalyst layer contains a catalyst, and any catalyst that participates in the cell reaction and can be used as a catalyst for a normal fuel cell can be used. Specifically, platinum-based metals can be preferably used.
[0046] Examples of platinum-based metals include platinum (Pt), palladium (Pd), ruthenium (Ru), iridium (Ir), osmium (Os), platinum-M alloys (wherein M is palladium (Pd), ruthenium (Ru), iridium (Ir), osmium (Os), gallium (Ga), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), silver (Ag), gold (Au), zinc (Zn), and tin. The platinum-based catalytic metal may include any one selected from the group consisting of platinum alloys and combinations thereof, and more preferably, a combination of two or more metals selected from the platinum-based catalytic metal group may be used, but is not limited thereto, and any platinum-based catalytic metal usable in the present technical field may be used without any restrictions.
[0047] Specifically, the platinum alloy may be selected from the group consisting of Pt-Pd, Pt-Sn, Pt-Mo, Pt-Cr, Pt-W, Pt-Ru, Pt-Ru-W, Pt-Ru-Mo, Pt-Ru-Rh-Ni, Pt-Ru-Sn-W, PT-Co, Pt-Co-Ni, Pt-Co-Fe, Pt-Co-Ir, Pt-Co-S, Pt-Co-P, Pt-Fe, Pt-Fe-Ir, Pt-Fe-S, Pt-Fe-P, Pt-Au-Co, Pt-Au-Fe, Pt-Au-Ni, Pt-Ni, Pt-Ni-Ir, Pt-Cr, Pt-Cr-Ir, and combinations thereof, and may be used alone or in combination of two or more.
[0048] In addition, the non-platinum alloy can be selected from the group consisting of Ir-Fe, Ir-Ru, Ir-Os, Co-Fe, Co-Ru, Co-Os, Rh-Fe, Rh-Ru, Rh-Os, Ir-Ru-Fe, Ir-Ru-Os, Rh-Ru-Fe, Rh-Ru-Os, and combinations thereof, and can be used alone or in combination of two or more.
[0049] Such a catalyst can be used as a catalyst black or can be supported on a carrier.
[0050] The support can be selected from carbon-based supports, porous inorganic oxides such as zirconia, alumina, titania, silica, and ceria, and zeolites. The carbon-based support may be selected from graphite, super P, carbon fiber, carbon sheet, carbon black, Ketjen Black, Denka Black, acetylene black, carbon nanotube (CNT), carbon sphere, carbon ribbon, fullerene, activated carbon, carbon nanofiber, carbon nanowire, carbon nanoball, carbon nanohorn, carbon nanocage, carbon nanoring, ordered nano- / meso-porous carbon, carbon aerogel, mesoporous carbon, graphene, stabilized carbon, activated carbon, and one or more combinations thereof, but is not limited thereto, and any support available in the art may be used without limitation.
[0051] The catalyst particles may be located on the surface of the support and may permeate the interior of the support, filling the interior pores of the support.
[0052] When using a precious metal supported on a carrier as a catalyst, a commercially available product may be used, or a catalyst produced by supporting a precious metal on a carrier may be used. The process of supporting a precious metal on a carrier is widely known in the art, and therefore, even if a detailed description is omitted in this specification, it is easily understandable to those who are engaged in the art.
[0053] The catalyst particles may be contained in an amount of 20 wt % to 80 wt % based on the total weight of the catalyst layers 10 and 30. If the amount is less than 20 wt %, there is a problem of reduced activity, and if the amount is more than 80 wt %, there is a problem of reduced catalytic activity due to agglomeration of the catalyst particles, which reduces the active area.
[0054] In addition, the catalyst layers 10 and 30 may contain a binder to improve adhesion and transport hydrogen ions. It is preferable to use an ionomer having ion conductivity as the binder. The ionomer has been described above, so a repeated description will be omitted.
[0055] However, the ionomer may be used alone or in the form of a mixture, and may be used selectively together with a non-conductive compound for the purpose of further improving the adhesive strength with the polymer electrolyte membrane 50. The amount of the ionomer used is preferably adjusted according to the purpose of use.
[0056] As the non-conductive compound, one or more selected from the group consisting of polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkylvinyl ether copolymer (PFA), ethylene / tetrafluoroethylene (ETFE), ethylene chlorotrifluoro-ethylene copolymer (ECTFE), polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer (pVdF-HFP), dodecylbenzenesulfonic acid, and sorbitol may be used.
[0057] The binder may be included in an amount of 20 wt % to 80 wt % based on the total weight of the catalyst layers 10 and 30. If the binder content is less than 20 wt %, the generated ions may not be transferred well, and if it exceeds 80 wt %, the pores may be insufficient to make it difficult to supply hydrogen or oxygen (air), and the active area for reaction may be reduced.
[0058] The electrode substrate may be a porous conductive substrate so that hydrogen or oxygen can be smoothly supplied. Representative examples include, but are not limited to, carbon paper, carbon cloth, carbon felt, or metal cloth (a porous film made of fibrous metal cloth or a cloth made of polymeric fibers on which a metal film is formed). In addition, it is preferable to use electrode substrates 40, 40' that have been treated with a fluorine-based resin for water repellency, since this prevents a decrease in the reactant diffusion efficiency due to water generated during the operation of the fuel cell. As the fluorine-based resin, polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, polyperfluoroalkylvinyl ether, polyperfluorosulfonyl fluoride alkoxyvinyl ether, fluorinated ethylene propylene, polychlorotrifluoroethylene, or copolymers thereof may be used.
[0059] Also, a microporous layer for enhancing the reactant diffusion effect in the electrode substrate may be further included. The microporous layer may include a conductive powder having a generally small particle size, such as carbon powder, carbon black, acetylene black, activated carbon, carbon fiber, fullerene, carbon nanotube, carbon nanowire, carbon nano-horn, or carbon nano ring.
[0060] The microporous layer is produced by coating a composition containing a conductive powder, a binder resin, and a solvent on an electrode substrate. As the binder resin, polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, polyperfluoroalkylvinyl ether, polyperfluorosulfonyl fluoride, alkoxyvinyl ether, polyvinyl alcohol, cellulose acetate, or copolymers thereof can be preferably used. As the solvent, alcohols such as ethanol, isopropyl alcohol, n-propyl alcohol, and butyl alcohol, water, dimethylacetamide, dimethylsulfoxide, N-methylpyrrolidone, and tetrahydrofuran can be preferably used.
[0061] The coating process may be performed by, but is not limited to, a screen printing method, a spray coating method, or a coating method using a doctor blade, depending on the viscosity of the composition.
[0062] A fuel cell according to another embodiment of the present invention may include a membrane electrode assembly according to an embodiment of the present invention.
[0063] FIG. 3 is a schematic diagram showing the overall configuration of the fuel cell.
[0064] Referring to FIG. 3, the fuel cell 200 includes a fuel supply unit 210 that supplies a mixed fuel obtained by mixing fuel and water, a reformer 220 that reforms the mixed fuel to generate a reformed gas containing hydrogen gas, a stack 230 in which the reformed gas containing hydrogen gas supplied from the reformer 220 undergoes an electrochemical reaction with an oxidant to generate electrical energy, and an oxidant supply unit 240 that supplies an oxidant to the reformer 220 and the stack 230.
[0065] The stack 230 includes a plurality of unit cells that generate electrical energy by inducing an oxidation / reduction reaction between the reformed gas, including hydrogen gas, supplied from the reformer 220 and the oxidant supplied from the oxidant supplying unit 240 .
[0066] Each unit cell means a unit cell that generates electricity, and includes a membrane electrode assembly that oxidizes / reduces oxygen in a reformed gas containing hydrogen gas and an oxidant, and a separator plate (also called a bipolar plate, hereinafter referred to as "separator plate") for supplying the reformed gas containing hydrogen gas and the oxidant to the membrane electrode assembly. The separator plates are placed on both sides of the membrane electrode assembly at the center. In this case, the separator plates located at the outermost sides of the stack are sometimes referred to as end plates.
[0067] One of the end plates of the separation plate is provided with a first pipe-shaped supply pipe 231 for injecting reformed gas containing hydrogen gas supplied from the reforming section 220, and a second pipe-shaped supply pipe 232 for injecting oxygen gas, and the other end plate is provided with a first exhaust pipe 233 for discharging reformed gas containing hydrogen gas that ultimately remains unreacted in the multiple unit cells to the outside, and a second exhaust pipe 234 for discharging oxidant that ultimately remains unreacted in the unit cells to the outside.
[0068] In the fuel cell, except that the membrane electrode assembly 100 according to one embodiment of the present invention is used, the separator, fuel supply unit and oxidant supply unit constituting the electricity generating unit are the same as those used in conventional fuel cells, and therefore detailed description thereof will be omitted in this specification.
[0069] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.
[0070]
[0071] [Example 1]
[0072] 0.32g of ZrOCl2·8HO and 2.0g of Pluronic P123 were dissolved in a 2.0M HCl aqueous solution, and then 4.2g of TEOS (tetraethylorthosilicate) was added and hydrolysis was carried out for 30 minutes at 35°C. 1.0g of TMB (trimethylbenzene) was added to the mixed solution and hydrolysis and condensation polymerization were carried out for 12 hours at 35°C. After that, it was hydrothermally treated at 90°C for 5 hours and then calcined at 550°C for 5 hours to produce plate-shaped mesopolis porous silica SBA.
[0073] A membrane electrode assembly was manufactured according to a conventional manufacturing method, except that the cathode was constructed using a first catalyst layer containing 5 wt% of the plate-shaped porous silica and a second catalyst layer containing no silica. At this time, the total thickness of the catalyst layers was 15 μm, and the thickness of the first catalyst layer was 3 μm. Nafion was used as the ionomer, and a platinum catalyst was used.
[0074] 5 is an optical microscope image of the surface of the first electrode layer (a) after formation of the first electrode layer in Example 1 and the surface of the first electrode layer (b) after the second electrode layer is formed on the first electrode layer. Referring to FIG. 1, if the size of the plate-like porous silica is large after the first electrode layer is formed (a), the surface of the first electrode layer will have an uneven shape. In the uneven surface of the first electrode layer, the part containing the porous silica is high and the part not containing the porous silica is relatively low, and such an uneven shape helps to improve the performance and durability of the membrane electrode assembly.
[0075]
[0076] [Example 2]
[0077] A membrane electrode assembly was prepared in the same manner as in Example 1, except that the second catalyst layer was not used.
[0078]
[0079] [Comparative Example 1]
[0080] A membrane electrode assembly was prepared in the same manner as in Example 1, except that spherical silica (50 nm) was used for the first catalyst layer.
[0081]
[0082] [Comparative Example 2]
[0083] 2.0 g of Pluronic P123 was dissolved in a 2.0 M HCl aqueous solution, and 4.2 g of TEOS (tetraethylorthosilicate) was added. Hydrolysis and condensation polymerization were carried out at 35°C for 12 hours, and then calcined at 550°C for 5 hours to produce normal mesopolis silica (not plate-shaped).
[0084] A membrane electrode assembly was prepared in the same manner as in Example 1, except that the first catalyst layer was made of the conventional mesophorous silica prepared above.
[0085]
[0086] [Comparative Example 3]
[0087] A membrane electrode assembly was manufactured in the same manner as in Example 1, except that the second catalyst layer contained 20 wt % of plate-shaped mesoporous silica.
[0088]
[0089] [Table 1]
[0090]
[0091] [Experimental example: Performance comparison of membrane electrode assemblies]
[0092] The performance of the membrane electrode assemblies according to the configurations in Table 1 in a low humidity environment (temperature: 80° C., humidity: RH 30%) was evaluated and is shown in Figure 6. Referring to Figure 6, in a low humidity environment, the voltages according to the current density of Examples 1 and 2 were measured to be significantly higher than those of Comparative Examples 1, 2, and 3. In particular, Example 1 including the second electrode layer showed excellent voltage even at the same current density, demonstrating the excellent effectiveness of the membrane electrode assemblies.
[0093]
[0094] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also fall within the scope of the present invention.
[0095]
[0096] [Explanation of symbols]
[0097] 100: Membrane electrode assembly
[0098] 1: Plate-shaped porous silica
[0099] 10, 30: Electrode
[0100] 11: First catalyst layer 12: Second catalyst layer
[0101] 20:Polymer electrolyte membrane
[0102] 200: Fuel cell 210: Fuel supply section
[0103] 220: Reforming section 230: Stack
[0104] 231: 1st supply pipe 232: 2nd supply pipe
[0105] 233: 1st discharge pipe 234: 2nd discharge pipe
[0106] 240: Oxidant supply unit
Claims
1. A first catalyst layer containing plate-shaped porous silica; and A membrane electrode assembly for a fuel cell comprising: a polymer electrolyte membrane.
2. 2. The fuel cell membrane electrode assembly according to claim 1, wherein the plate-like porous silica comprises mesopores having a morphology perpendicular to the plate-like morphology.
3. 2. The membrane electrode assembly for a fuel cell according to claim 1, wherein the plate-shaped porous silica has pores with a diameter of 2 to 40 nm.
4. 2. The membrane electrode assembly for a fuel cell according to claim 1, wherein the plate-shaped porous silica has a size of 50 to 2,000 nm.
5. 2. The membrane electrode assembly for a fuel cell according to claim 1, wherein the plate-shaped porous silica has a thickness of 30 to 300 nm.
6. 2. The membrane electrode assembly for a fuel cell according to claim 1, wherein the plate-shaped porous silica in the first catalyst layer is contained in an amount of 1 to 20 wt % based on the total weight of the first catalyst layer.
7. 2. The membrane electrode assembly for a fuel cell according to claim 1, wherein the ionomer content of the first catalyst layer is 34 to 40 wt % based on the total weight of the first catalyst layer.
8. 2. The fuel cell membrane electrode assembly of claim 1, wherein the first catalyst layer has a thickness of 0.2 to 5 [mu]m.
9. 2. The fuel cell membrane electrode assembly according to claim 1, wherein the first catalyst layer is located between the polymer electrolyte membrane and a second catalyst layer that does not contain or contains a smaller amount of plate-shaped porous silica.
10. 10. The fuel cell membrane electrode assembly of claim 9, wherein the ionomer content of the first catalyst layer is greater than the ionomer content of the second catalyst layer.
11. A fuel cell comprising the fuel cell membrane electrode assembly of any one of claims 1 to 10.
Citation Information
Patent Citations
Polymer solid-electrolyte fuel cell
JP1994111827A
Surface electrolyte sefc for fuel cell
JP2006066390A
Fuel cell
JP2019139886A
Catalyst for oxygen reduction reaction, fuel cell including the catalyst and method for preparing the catalyst
KR101615570B1
